Migration, belonging and the nation state - Babacan, Alperhan; Singh, Supriya (Cambridge Scholars, 2010)
"The book questions how modern migration and globalisation have impacted upon notions of belonging and identity within nation-states across the world. This book provides theoretical and empirical accounts of the relationship between identity, rights nationalism, race and ethnicity. The authors cover the complexity of the topic as identification has become much more multifaceted. The authors cover difficult and cutting edge issues relating to citizenship, nation formation, identity, remittances, transnational families, migration and asylum in the context of Australia, Malaysia, Pakistan and Sri Lanka. These critical issues inform and shape key policy and program responses of many governments and are subject of topic in international relations forums between nation states."--Publisher description from jacket.